Strategi Guru dalam Mengembangkan Pembelajaran Berdiferensiasi untuk Siswa Slow Learner di Sekolah Dasar - Prahastiwi, Eka Danik; Zuriah, Nurul; Widodo, Joko (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study aims to examine teachers' strategies in developing differentiated instruction for slow learner students in elementary schools, particularly at MI Adab and Tahfidz Baleharjo, Pacitan. The research is grounded in the context of the Merdeka Curriculum, which emphasizes inclusive and responsive learning tailored to the diverse needs of students. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The research subjects included the principal and a fifth-grade teacher. The findings reveal that while the teacher has a basic understanding of slow learner characteristics, the implementation of differentiated instruction strategies is not yet optimal. Adjustments in instructional time, content, and learning processes have begun but remain general and unstructured. Continuous training and mentoring are needed to enable teachers to design more adaptive, effective, and individualized learning services for slow learner students. Keywords: differentiated instruction, slow learner students, elementary school, Merdeka Curriculum